A series of terpyridine-based zinc(ii) complexes assembled for third-order nonlinear optical responses in the near-infrared region and recognizing lipid membranes. Issue 31 (31st July 2017) - Tang, Yiwen; Kong, Ming; Tian, Xiaohe; Wang, Jinghang; Xie, Qingyuan; Wang, Aidong; Zhang, Qiong; Zhou, Hongping; Wu, Jieying; Tian, Yupeng
Abstract : Two-photon (TP) microscopy has advantages for biological imaging in that it allows deeper tissue-penetration and excellent resolution compared with one-photon (OP) microscopy. Abstract : Two-photon (TP) microscopy has advantages for biological imaging in that it allows deeper tissue-penetration and excellent resolution compared with one-photon (OP) microscopy. Herein, two-photon activated nonlinear optical (NLO) materials, a terpyridine derivative ligand with a donor–acceptor (D–A) model and its corresponding four zinc(ii ) complexes (Z1–Z4 ), were assembled and fully characterized. Based on their systematic photophysical investigations, it was found that the third-order NLO response in the near-infrared (NIR) region was significantly enhanced for the symmetrical complexZ4 compared with the other asymmetric complexes (Z1–Z3 ). To further explore its utility in biological systems, Z4 was selected as a two-photon probe for cellular lipid membranes, which was confirmed both by two-photon confocal microscopy and transmission electron microscopy (TEM). Furthermore, it was found that the fluorescence intensity was enhanced for complexZ4 with the addition of bioactive liposomes (1 μg mL −1 ). Its recognition mechanism was demonstrated by experimental methods, as well as molecular modeling calculations. These findings should open a new pathway for functional metal complexes as lipid membrane targeting probes.